Multi-layered ZnS/CdS Anti–Reflection Coating by Spray Pyrolysis with Nebulizer - Sawsan H. Abdullah; Khalil I. Inad; Ahmed S. Jaber; Salam Waley (Universitas Sebelas Maret (UNS), 2026)
To produce a ZnS thin film for this article, a thin film of ZnS using spray pyrolysis has been synthesized as thin films of ZnS by spray pyrolysis technique based on ZnS as spray pyrolysis. The study targets a multi-layer anti-reflective coating that consists of ZnS and CdS layers using a modified spray pyrolysis with the ultrasonic atomizer. The aim is to analyze the effect of this coating on the structural and optical properties, notably with regard to transmittance, reflectivity, and Raman analysis. Here, two different thin film layers were deposited with different structure types, which include cubic and hexagonal phases to achieve the obtained thin films with spray pyrolysis. Multilayer zinc sulfide (ZnS) is described to be an effective and inexpensive anti-reflective film that can be used as a solar cell coating. There exists both phases and this is confirmed by XRD analysis. The average grain size and the surface smoothness of the two-layer films was smaller than that of the other films, whereas the specific surface area was high as reported by AFM studies. The CdS/ZnS thin films showed significantly less reflectivity compared to other thin films based on optical measurements using UV-visible spectroscopy and calculated reflectivity from predefined refractive index-band gap correlation analysis.